Perancangan Strategi terhadap Bisnis Fashion Muslim (Studi Kasus: PT. Fatahillah Anugerah Nibras) - Lindawati Kartika; Rikrik Riesmawan; Mokhamad Syaefudin Andrianto; Hardiana Widyastuti; Lindawaty (IPB University, 2023)
Initiatives to restore the economy in Indonesia have continued after the COVID-19 pandemic. The decline in people's purchasing power due to the pandemic is a threat to companies. Therefore, the right strategy is needed to deal with this threat, including PT. Fatahillah Anugerah Nibras, which has been a company in the fashion sector since 2011. The purpose of this research is to identify and analyze the company's internal and external environment through the Business Model Canvas (BMC) and SWOT analysis, formulate and assess the company's Key Performance Indicators (KPIs) based on the Balanced Scorecard (BSC). This study uses a quantitative approach, with primary data sourced from questionnaires and secondary data sourced from literature studies. The results of the analysis of the internal and external environment show that PT. Fatahillah Anugerah Nibras is in quadrant IV, which means that the company is in a period of growth and a strategy is needed to increase the business growth. Meanwhile, the results of the BSC analysis show that the majority of KPIs scores are in the good category, but there are still a number of things that need to be improved, especially from an internal business process and financial perspective. Therefore, by implementing several strategies that drive business growth and improve several aspects of internal and financial processes, it is hoped that the business will run more effectively and efficiently.